Are Functional Performance Test Scores Better When Compared to Baseline or Contralateral Limb Scores Following LE Injury in Adolescent Athletes? - Edward Jones; Jessica Jochum; Hannah Corn; Michaela O'Brien; Melissa Parks; Jamal Armoush; Amanda Annee (International Journal of Sports Physical Therapy)
# Background